Dietary Principles, Interventions and Oxidative Stress in Psoriasis Management: Current and Future Perspectives - Oana-Georgiana Vaduva; Aristodemos-Theodoros Periferakis; Roxana Elena Doncu; Vlad Mihai Voiculescu; Calin Giurcaneanu (Medicina)
Psoriasis is a chronic inflammatory autoimmune disease that causes significant deterioration of the quality of life, and due to its multifactorial causes, it is often difficult to manage. Apart from genetic and environmental components, an important part of its pathophysiology comprises an oxidative stress induction that the standard antioxidative mechanisms of the human body cannot compensate for. Moreover, in many psoriatic patients, there is a documented imbalance between antioxidant and pro-oxidative factors. Usually, psoriasis is evaluated using the Psoriasis Area and Severity Index (PASI) score. It has been demonstrated that dietary choices can lead to significant modification of PASI scores. Hypocaloric diets that are rich in antioxidants are highly effective in this regard, especially when focusing on vegetables and restricting consumption of animal-derived protein. Specific dietary regimens, namely the Mediterranean diet and potentially the ketogenic diet, are very beneficial, in the former case owing in large part to the omega-three fatty acids it provides and its ability to alter gut microbiome, a factor which seems to play a notable role in the pathogenesis of the disease. Another option is the topical application of vitamin D and its analogues, combined with corticosteroids, which can ameliorate the manifestations of psoriasis at the level of the skin. Finally, oral vitamin D supplementation has a positive impact on psoriatic arthritis and can mitigate the risk of associated comorbidities.